Adhesion controls bacterial actin polymerization-based movement - Soo, Frederick S. (National Academy of Sciences, 2005)
As part of its infectious life cycle, the bacterial pathogen Listeria monocytogenes propels itself through the host-cell cytoplasm by triggering the polymerization of host-cell actin near the bacterial surface, harnessing the activity of several cytoskeletal proteins used during actin-based cell crawling. To distinguish among several classes of biophysical models of actin-based bacterial movement, we used a high-throughput tracking technique to record the movement of many individual bacteria during temperature shifts. The speed of each bacterium varied strongly with temperature, closely following the Arrhenius rate law. Among bacteria, the prefactor A of the Arrhenius dependence unexpectedly varied exponentially with apparent activation energy, E(a), over a wide range (8–21 kcal/mol), reminiscent of the “rate compensation effect” of classical catalytic reactions. Average E(a) were increased for mutant bacteria deficient in binding Ena/VASP proteins and bacteria moving in diluted extract. These two effects were additive. The observed temperature and rate compensation effects are consistent with a class of simple kinetic models in which the bacterium advances through the thermally driven, cooperative breakage of groups of adhesive bonds on its surface. The estimated number of coupled adhesive bonds N on the bacterial surface varies between 10 and 40 bonds. In contrast to other models, this model correctly predicts an experimentally observed negative correlation between bacterial speed and actin gel density. The idea that speed depends on adhesion, rather than polymerization, suggests several alternative mechanisms by which known cytoskeletal regulatory proteins could control cellular movement.